Same Phenotype in Children with Growth Hormone Deficiency and Resistance - Irene Ioimo; Carmen Guarracino; Cristina Meazza; Horacio M. Domené; Mauro Bozzola (Hindawi Limited, 2018)
By definition, about 2.5% of children show a short stature due to several causes. Two clinical conditions are characterized by serum IGF-I low levels, idiopathic GH deficiency (IGHD), and GH insensitivity (GHI), and the phenotypic appearance of these patients may be very similar. We studied two children with short stature and similar phenotypes. The first case showed frontal bossing, doll face, acromicria, and truncal obesity, with a GH peak <0.05 ng/ml after stimuli and undetectable serum IGF-I levels. After PCR amplification of the whole GH1 gene, type IA idiopathic GHD was diagnosed. The second case had cranium hypoplasia, a large head, protruding forehead, saddle nose, underdeveloped mandible, and a micropenis. Basal GH levels were high (28.4 ng/ml) while serum IGF-I levels were low and unchangeable during the IGF-I generation test. Laron syndrome was confirmed after the molecular analysis of the GH receptor (GHR) gene. IGHD type IA and Laron syndrome is characterized by opposite circulating levels of GH, while both have reduced levels of IGF-I, with an overlapping clinical phenotype, lacking the effects of IGF-I on cartilage. These classical cases show the importance of differential diagnosis in children with severe short stature.